Performing reactive power compensation of three-phase induction motor by using parallel active power filter - Karaman, Ömer Ali; Gundogdu, Ahmet; Cebeci, Mehmet (My University, 2020)
Nowadays, the problem of power quality increases day by day. Harmonic current and reactivepower are the important factors disturbing the power quality. The induction motors draw bothharmonic current and reactive power from the grid. Reactive power and harmonic current leadto heat losses and decrease in the efficiency of the transmission lines. Passive and active filterapplications have been used to solve these problems. There are some disadvantages of passivefilters. Large physical dimensions and resonance with load can be shown as examples for thesedisadvantages. Therefore, the application areas of Active Power Filter (APF) are rapidlydeveloping due to the fact that they can be applied together with harmonic and reactive powercompensation as appropriate control methods. This paper proposes a MATLAB/Simulinksimulation to perform power factor correction and reactive power compensation of three-phaseinduction motor by using three-phase Parallel Active Power Filter (PAPF). In order to generatePAPF’s reference currents the Sine Multiplication Technique (SMT) is used. Simulation studiesare presented to be able to assess the performances under different motor operating conditions.The proposed hysteresis controller based PAPF filter makes the power factor up to 1 and thereactive power compensation of the three-phase induction motor.
Keywords: Harmonics; Parallel active power filter; Power factor correction; 3-phase induction motor